1978
DOI: 10.1002/dev.420110603
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature and 5‐hydroxytryptamine during early postnatal maturation in mice

Abstract: A relationship between the maturational increases in body temperature and brain indoleamines has been explored through altering brain 5-hydroxytryptamine (5-HT) content. Effects on body temperature at approximately constant ambient temperature (about 24 degrees C) have been studied following pharmacological manipulations in mice up to 16 days postpartum. Administration of 5-hydroxytryptophan (5-HTP) to increase 5-HT levels was associated with decreased body temperature throughout the maturational period. Deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, the functions of central and peripheral 5-HT differ, with hypothalamic 5-HT serving as an important neurotransmitter involved in regulating physiological processes such as sleep, emotion, and body temperature [ 74 76 ]. It has been reported that the tryptophan–5-HT metabolic pathway in the hypothalamus is involved in the regulation of brain neurotransmitters, and central 5-HT administration can activate 5-HTergic neurons to cause hypothermia in mice and chicks [ 77 , 78 ]. Exogenous tryptophan supplementation can also increase hypothalamic 5-HT levels, lowering the rectal temperature in broiler chickens and indicating a negative correlation between central 5-HT content and heat production [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the functions of central and peripheral 5-HT differ, with hypothalamic 5-HT serving as an important neurotransmitter involved in regulating physiological processes such as sleep, emotion, and body temperature [ 74 76 ]. It has been reported that the tryptophan–5-HT metabolic pathway in the hypothalamus is involved in the regulation of brain neurotransmitters, and central 5-HT administration can activate 5-HTergic neurons to cause hypothermia in mice and chicks [ 77 , 78 ]. Exogenous tryptophan supplementation can also increase hypothalamic 5-HT levels, lowering the rectal temperature in broiler chickens and indicating a negative correlation between central 5-HT content and heat production [ 20 ].…”
Section: Discussionmentioning
confidence: 99%